Tales from Kentucky doctors - Montell, William Lynwood, 1931- (University Press of Kentucky, 2008)
In Tales from Kentucky Doctors, noted oral historian William Lynwood Montell has assembled a fascinating collection of memoirs from Kentucky's medical providers. Ranging from humorous to heartwarming to tragic, the stories presented in Tales from Kentucky Doctors are authentic and captivating. While these firsthand accounts from and about Kentucky doctors won't be found in a formal history book, this collection is essential reading for anyone who wishes to understand the culture and tradition of Kentucky medical practice. By combining personal experiences, humorous anecdotes, and local legends.